Effects of bridging atom and π-bridge length on physical and photovoltaic properties of A-π-D-π-A oligomers for solution-processed organic solar cells - Luponosov, Yuriy N.; Min, Jie; Bakirov, Artem V.; Dmitryakov, Petr V.; Chvalun, Sergei N.; Peregudova, Svetlana M.; Ameri, Tayebeh; Brabec, Christoph; Ponomarenko, Sergei A. (Dyes and Pigments, 2015)
Synthesis of novel acceptor-donor-acceptor oligomers with electron-withdrawing alkyldicyanovinyl groups linked through an oligothiophene π-bridge with either dithienosilole or cyclopentadithiophene electron donor units is described. Changing the bridgehead atom from carbon to silicon in the central donor unit leads to a significant change in optical, thermal and structural properties of the oligomers. In addition, elongation of the oligothiophene π-bridge in the oligomers increases energies of HOMO and LUMO levels and leads to an unexpected hypsochromic shift of their absorption spectrum, because extension of the conjugation length cannot compensate a decrease of the intramolecular charge transfer between the dithienosilole and dicyanovinyl units. Although these minor changes in the chemical structures have a pronounced impact on the morphologies of their blends with PC70BM, the optimized solution-processed organic solar cells based on these small molecules demonstrate similar power conversion efficiencies.
EAM Import::2019-03-14
Keywords: Alkyldicyanovinyl groups; Dithienosilole; Donor-acceptor oligomers; Effect of heteroatom substitution; Oligothiophenes; Organic solar cells